Penerapan Metode Equivalence Partitioning Pada Pengujian Otomatis Sistem Perhitungan Dasar Pengenaan Pajak Kendaraan Dan Bea - Gustika Barlina Mitra; Imam Asrowardi; Eko Subyantoro (Ikatan Ahli Informatika Indonesia, 2023)
PT. Microdata Indonesia is a company that provides information technology consulting services, with the main focus on developing Information Technology (IT) products. The products produced aim to be solutions for various segments and institutions. Development of a basic calculation system for the imposition of motor vehicle taxes and duties in Indonesia by PT. Microdata Indonesia focuses on factors such as vehicle type, engine capacity, vehicle age, and other relevant factors. The main objective of this research is to ensure that the developed system achieves a high level of accuracy in tax calculations, with the use of automated testing methods, especially Equivalence Partitions, which divides input data into equality classes. The results of this test were that the system worked well and no errors were found in the functions tested, so it was concluded that the basic calculation system for vehicle taxes and duties that they had developed was ready to be used.